Pemberdayaan Ekonomi Ibu Rumah Tangga melalui Produksi Kripik Tempe di Desa Nambangrejo Sukorejo Ponorogo - Sintha Mawarni; Suad Fikriawan; Tsalits Maratun Nafiah (Social Science Academic, 2025)
One of the villages in Sukorejo, Nambangrejo Village is one of the villages producing tempe chips. Community service activities in Nambangrejo Village take the form of community empowerment through economic empowerment of housewives through tempe production. This economic empowerment is due to business conditions that are not optimal, so it is necessary to provide economic empowerment for housewives through a product. The aim of this service is to improve the economy of housewives in Nambangrejo Village, Sukorejo District. The method used is the Asset Based Community Development (ABCD) method. Students realize this method by holding a Digital Marketing Workshop aimed at business people and youth in Nambangrejo Village, Sukorejo District, Ponorogo Regency.